2014
DOI: 10.1186/s13059-014-0492-1
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic analysis reveals tomato genes whose expression is induced specifically during effector-triggered immunity and identifies the Epk1 protein kinase which is required for the host response to three bacterial effector proteins

Abstract: BackgroundPlants have two related immune systems to defend themselves against pathogen attack. Initially, pattern-triggered immunity is activated upon recognition of microbe-associated molecular patterns by pattern recognition receptors. Pathogenic bacteria deliver effector proteins into the plant cell that interfere with this immune response and promote disease. However, some plants express resistance proteins that detect the presence of specific effectors leading to a robust defense response referred to as e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
84
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 82 publications
(91 citation statements)
references
References 66 publications
4
84
3
Order By: Relevance
“…As observed for the PTI reporter gene, the activation of the ETI marker gene was over-estimated. Additionally, the gene expression reduction between 6 and 12 h previously reported18, could not be observed when using GAPDH normalization. Again, the combined use of ARD2 / VIN3 leads to a drastic reduction in standard deviation values.…”
Section: Resultsmentioning
confidence: 69%
See 1 more Smart Citation
“…As observed for the PTI reporter gene, the activation of the ETI marker gene was over-estimated. Additionally, the gene expression reduction between 6 and 12 h previously reported18, could not be observed when using GAPDH normalization. Again, the combined use of ARD2 / VIN3 leads to a drastic reduction in standard deviation values.…”
Section: Resultsmentioning
confidence: 69%
“…To validate the selection of reference genes, we measured the expression of a PTI- and an ETI-specific gene that were previously reported18. As recommended51, we estimated the relative expression using the normalization factor NF calculated as the geometric mean of Cq values obtained for ARD2 and VIN3 , the most stable reference genes.…”
Section: Resultsmentioning
confidence: 99%
“…A VIGS forward screen in N. benthamiana for PTI genes revealed surprisingly few essential genes and no silver-bullet candidates for the PTI-protected state (Chakravarthy et al, 2010). However, RNA-seq transcription profiling aimed at distinguishing PTI and ETI responses of tomato to DC3000 derivatives revealed enrichment for genes associated with the phenylpropanoid pathway in the PTI-specific set (Pombo et al, 2014). Phenylpropanoid pathway genes were similarly found in a transcriptome study of PTI genes in tobacco (Szatmari et al, 2014), and the N. benthamiana VIGS screen identified the CA4H gene which plays a role in phenylpropanoid biosynthesis (Chakravarthy et al, 2010).…”
Section: Blocking Of Pti Implementationmentioning
confidence: 99%
“…NormFinder uses a model-based approach allowing intra-and intergroup comparisons of the obtained Ct values, and it provides a ranking of the candidate reference genes based on the estimated standard deviations. Recent studies have proposed different reference genes for expression studies during tomato (Solanum lycopersicum) development (Expósito-Rodríguez, Borges, Borges-Pérez, & Pérez, 2008) and tomato-pathogen interactions (Fradin et al, 2009;Müller et al, 2015;Pombo et al, 2014). Primer pairs for ten of these genes-four classical housekeeping genes, such as elongation factor EF1-α and ATPase (Expósito-Rodríguez et al, 2008;Pombo et al, 2014), and six newly suggested ones (Müller et al, 2015;Pombo et al, 2014)-were selected and evaluated in tomato-grey mould interaction.…”
Section: Introductionmentioning
confidence: 99%
“…tomato interaction. The pathogen-leaf infiltrations were performed on whole plants from which leaf samples were harvested at 3, 6, 9 and 12 hrs postinoculation (hpi) (Pombo et al, 2014). Primers amplifying importin β (primer set IMPβ), PHD finger family protein (PHD), cytochrome c oxidase subunit (COX), polyribonucleotide 5′-hydroxyl-kinase (CLP1) and U6 snR-NA-associated Sm-like protein LSm7 (LSM7) were used in a tomato (cv.…”
Section: Introductionmentioning
confidence: 99%